Divergence and ranking of taxa across the kingdoms Animalia, Fungi and Plantae - M. C. Samarakoon (2018)
© Guizhou Academy of Agricultural Sciences. In science, species are grouped and ranked in kingdoms, phyla, classes, orders, families and genera and several other intermediate taxa, in a taxonomic hierarchy. However, the ranking of phyla, classes, orders and families across kingdoms is not linked and there is unlikely to be any correlation between these ranks in animals, fungi or plants. In a few recent studies, divergence times have been used to develop more natural groupings within ranks and it has been suggested that divergence times should be used as a universal criterion in high level ranking. It would therefore be desirable to develop more stable and standardized grouping of taxa in phyla, classes, orders and families across the kingdoms using divergence times. However, is this feasible? The origins of the kingdoms have been well-studied, however a comparison of the earliest divergence of major taxa (phyla, classes, orders, and families) across these kingdoms is lacking. We therefore considered that it would be of interest to look at ranking of groups across three kingdoms, Animalia, Fungi and Plantae. Are the ranking in these kingdoms comparable or has one or more kingdoms been more liberal in splitting taxa at the higher levels (e.g phyla, classes, orders, families)? We used paleobiological information from early diverged groups among the kingdoms Animalia, Fungi and Plantae corresponding to the geological time scale for comparisons. As a general rule, we found that groups of Animalia classified as phyla, classes, orders and families, diverged earlier as compared to those of the kingdoms Fungi and Plantae. This suggests that animal taxonomists have been more liberal when splitting ranks at the phylum, class and order levels, while at the family level the ranking across kingdoms is comparable. The common trend of evolutionary events could therefore be applied for re-ranking of some groups, especially at the generic and perhaps family levels. However, it would appear an impossible task to standardize higher level rankings across the kingdoms, as there would need to be huge, and probably unacceptable changes. Basically, the mycologists and botanists would need to split much more at the phylum, class and order levels, while the zoologists would need to combine many of their phyla, classes and orders. The data however, suggests that fungal and plant taxonomists could be more liberal when considering new families, orders, classes and phyla in the future.